2017
DOI: 10.1080/2000656x.2016.1269777
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative vasopressors and thrombotic complications in free flap breast reconstruction

Abstract: This study demonstrates that the use of intraoperative vasopressor agents in the anaesthetic care of free flap breast reconstruction patients is common, but likely does not impact thrombotic events or flap loss. Minor complications may, however, be more common in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…A variety of defects were reconstructed, most commonly of the head and neck 13,15,16,[19][20][21][22][23][24]26 and breast. 14,16,18,23,25,27 Most studies reported no significant association between vasopressor use and the outcome measures of this study. Isolated studies found increased pedicle thrombosis with postoperative vasopressor use (OR: 3.40, p < 0.05) 22 and increased flap-related complications with intraoperative vasopressor use (OR: 1.67, p < 0.01).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…A variety of defects were reconstructed, most commonly of the head and neck 13,15,16,[19][20][21][22][23][24]26 and breast. 14,16,18,23,25,27 Most studies reported no significant association between vasopressor use and the outcome measures of this study. Isolated studies found increased pedicle thrombosis with postoperative vasopressor use (OR: 3.40, p < 0.05) 22 and increased flap-related complications with intraoperative vasopressor use (OR: 1.67, p < 0.01).…”
Section: Resultsmentioning
confidence: 57%
“…Isolated studies found increased pedicle thrombosis with postoperative vasopressor use (OR: 3.40, p < 0.05) 22 and increased flap-related complications with intraoperative vasopressor use (OR: 1.67, p < 0.01). 25 Interestingly, some studies found that vasopressor use was associated with less free flap failure (OR: 0.56, p ¼ 0.02; OR: 0.16, p ¼ 0.04), 16,19 microvascular thrombosis (OR: 0.59, p < 0.01), 16 and overall flap complications (OR: 0.25, p ¼ 0.05). 19 One study found that vasopressors did not affect arterial thrombosis rates but were instead associated with a lower risk of venous congestion (OR: 0.60, p ¼ 0.018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations